Trends and prospects for cassava in the developing world - Sarma, J. S.; Kunchai, Darunee. (International Food Policy Research Institute, 1991)
Cassava is a relatively neglected tropical root crop. Important in the economy of poor households, cassava is one of the major sources of subsistence and cash income to farmers in agroclimatically disadvantaged regions. It is a major staple food in several countries of Sub-Saharan Africa, Latin America, and Asia.Besides its direct use as food, cassava is also used as feed for livestock and poultry and as raw material for manufactured starch, tapioca and snack foods.